The Effect of Problem Based Learning Model Aided by Animation Media on Interests and Learning Outcomes of Class V Elementary School Social Sciences - Rustinah R; Muhammad Basri; Muhajir M (Universitas Pendidikan Indonesia (UPI), 2021)
This research aims to find out the influence of problem based learning model assisted by animation media on students' learning interests and social learning outcomes of class V in state Elementary School 3 Connect Java Pangkep Regency. The type of research was Quasi Experimental Design using nonequivalent control group design, this study applied saturated sample of 40 students with 2 classes as control classes and experimental classes. The data was analyzed using SPSS 21.0. Data collection in order to get the students' learning results was obtained by using pretest and posttest and to get the results of students' learning interest obtained by using questionnaires. The results of descriptive analysis in terms of interest and learning results of experimental classes were higher than the control class. in addition, there is a gap in the control class where the interest in learning is not balanced with the learning outcomes. Then on Manove-test obtained a significance of 0.000. This significance value was less than 0.05, which mean there was an influence of problem based learning models assisted by animation media simultaneously on interest and learning outcomes. Based on the results of this study, it can be concluded that there was an influence of problem based learning assisted by animation media on the students' interests and learning outcomes of social science students of class V in State Elementary School 3 Connect Jawa Pangkep Regency. which mean there was an influence of problem based learning models assisted by animation media simultaneously on interest and learning outcomes. Based on the results of this study, it can be concluded that there was an influence of problem based learning assisted by animation media on the students' interests and learning outcomes of social science students of class V in State Elementary School 3 Connect Jawa Pangkep Regency. which mean there was an influence of problem based learning models assisted by animation media simultaneously on interest and learning outcomes. Based on the results of this study, it can be concluded that there was an influence of problem based learning assisted by animation media on the students' interests and learning outcomes of social science students of class V in State Elementary School 3 Connect Jawa Pangkep Regency.